Improving Outcomes for Displaced Rohingya People and Hosts in Cox’s Bazar : Current Evidence and Knowledge Gaps - Raza, Wameq Azfar (World Bank, Washington, DC, 2021)
Since August 2017, more than 725,000 Displaced Rohingya People (DRP) have crossed into Bangladesh from Rakhine State in Myanmar. The influx has resulted in a protracted humanitarian crisis, as hundreds of thousands of DRP have settled into largely makeshift camps in the Cox’s Bazar (CXB) district. The DRP remain almost entirely reliant on humanitarian assistance for food, shelter, education, and healthcare. Bangladeshi host communities (HC) in the affected areas faced difficult economic conditions before 2017, and the arrival of Rohingya may have exacerbated some of these challenges. Currently, as the crisis in CXB extends due to uncertain plans for Rohingya repatriation, a review of available evidence is needed to inform the ongoing humanitarian response and guide subsequent analytical research on inclusive development outcomes for both DRP and host communities. In addition to implementing humanitarian programs in the Rohingya response, several organizations, including the World Bank, are generating knowledge products to improve the results of humanitarian action in CXB and advance longer-term development goals. The literature generated thus far is heterogeneous in approach, methods, and quality. To date, no study exists that synthesizes the findings from these studies to provide an overview for policy makers and researchers. This paper aims to identify knowledge gaps through a rapid evidence assessment of literature on the CXB region, the DRPs, and the HC. By mapping the current evidence and knowledge gaps around improving outcomes for the DRP and HC, this paper intends to provide national stakeholders, development agencies, and their partners with a holistic picture of the analytical work taking place on the ground and to indicate further research that may be needed during the ongoing humanitarian and development response.